Phenotypic and genotypic characterization of Salmonella enterica serovar Typhimurium and Salmonella enterica serovar Enteritidis in Malaysia / Ngoi Soo Tein - Ngoi , Soo Tein (2018)
Salmonella enterica serovar Typhimurium (S. Typhimurium) and Salmonella enterica serovar Enteritidis (S. Enteritidis) are the two most common non-typhoidal Salmonella serovars causing salmonellosis in humans. In Malaysia, these two serovars are often isolated from food and animals but there are limited studies which focused on detailed genotypic and phenotypic characterization of these organisms. The overall goal of this study was to determine the genotypic and phenotypic characteristics of these two major Salmonella serovars circulating in Malaysia, in order to understand the epidemiology and pathogenicity of these organisms in this region. A total of 84 S. Typhimurium and 111 S. Enteritidis strains isolated from food, animals, and humans were examined in this study. Both genotyping methods, namely pulsed-field gel electrophoresis (PFGE) and multiple-locus variable number tandem repeat analysis (MLVA), used in this study showed a limited genetic diversity among the Salmonella strains circulating in Malaysia. In fact, the S. Enteritidis strains were highly clonal, with most of the strains being single-locus variants, regardless of their sources. Although MLVA was found to be overall less discriminative than PFGE, it was able to complement the latter in further differentiating the strains with identical pulsotypes. Fifty percent of the S. Typhimurium strains and 39 % of the S. Enteritidis strains were multi-drug resistant. High rates of resistance towards ampicillin, nalidixic acid, streptomycin, sulphonamides, sulfamethoxazole, tetracycline, and trimethoprim were observed among the strains. Upon close examination on the quinolone resistance mechanisms, the major factor that contributed to such resistance was mutations in the gyrA gene. Two novel mutations in the parE gene, and the plasmid-borne qnrS1 gene (found in 30 % of the quinolone-resistant strains) might have contributed to the reduced susceptibility to ciprofloxacin (fluoroquinolone). A high resolution melting curve assay was successfully developed for rapid screening of mutations in the quinolone-resistant determining regions of the gyrase and topoisomerase IV genes, which confer resistance to quinolones and fluoroquinolones. A monophasic variant of S. Typhimurium was identified, and the genomic deletion spanning the fljAB, hin, partial iroB, STM2757, and STM2758 genes has resulted in the monophasic phenotype of this strain. The genomes of the endemic S. Typhimurium strains were essentially identical except for minor genetic variations in the phage- and plasmid-associated regions. Phylogenetic analyses showed that the S. Typhimurium strains in Malaysia were closely related to global S. Typhimurium strains with highly virulent phenotypes. Multiple antimicrobial resistance and virulence determinants were identified in the biphasic genomes. In conclusion, S. Typhimurium and S. Enteritidis strains circulating in Malaysia were genetically homogeneous, with a high rate of multi-drug resistance. The rarely reported monophasic variant of S. Typhimurium isolated in Malaysia showed unique fljAB operon deletion pattern. Local S. Typhimurium strains in Malaysia possess virulence potential to cause severe infections in humans and animals.